Influence of human placenta extracts to erythrocytes' thermohemolysis - Bobrova, O.M.; Govorova, Yu.S.; Nardid, O.A.; Repina, S.V.; Narozhnyi, S.V.; Pokryshko, S.V. (Reports of the National Academy of Sciences of Ukraine, 2018)
The influence of the freezing of human placenta extracts on their ability to reduce the thermohemolysis of erythrocytes has been investigated. It has been shown that the freezing of placenta extracts down to −2 and −19 °C and the following heating do not lead to a significant change in their effectiveness to stabilize the erythrocyte membranes at temperature effects. The placenta extract fractions, namely less than 4 kDa and 12—20 kDa, most effectively reducing the level of erythrocytes' thermohemolysis, have been identified. The percentages of inhibition of the thermogemolysis for them are (31.7 ± 3.3) % and (31.5 ± 3.2) %, respectively.